Is enterprise value affected by political nominations for a regulatory agency's presidency? - Sassi, Guilherme Scotto (2013)
Economists have argued that regulation is the appropriate approach to maintain output in its economically efficient level in a natural monopoly, and that can be achieved by submitting these companies to regulatory agencies’ decisions. The autonomous agencies are, however, not free in an absolute sense, and it is important to ask what the priorities of the new administration are. One answer is that it is designed to give leeway and powers of discretion to unbiased professionals with expertise in their field. In practice, however, professional experts might often be politically motivated. The objective of this study is to investigate whether political nominations to the presidency of regulatory agencies, rather than technical appointments, affect the level of regulatory risk. In order to achieve this purpose, an event study was performed, where the regulatory risk in a political nomination will be compared to a technical nomination, in terms of abnormal return.